Immunopathological studies in the ovine lung during the course of natural and experimental maedi-visna virus infection - Begara, Isabel Maria (The University of Edinburgh, 1994)
The pulmonary immunopathology of maedi-visna virus (MVV) infection was investigated, firstly performing in vivo, and in vitro studies and secondly, by reproducing the disease experimentally.

Peripheral blood (PB) and bronchoalveolar lavage fluid (BALF) cells of naturally MVVinfected and control sheep were phenotypically characterised by using single-colour flow cytometry. BALF from MW-infected sheep had significandy increased percentages of lymphocytes, neutrophils and CD8+ lymphocytes, decreased percentages of CD4+ and CD5* lymphocytes (p< 0.05), significant (p< 0.001) inversion of the CD4+/CDS* ratio, increased MHC Class II expression on BALF macrophages and upregulated expression of LFA-1 and LFA-3 on BALF lymphocytes (p< 0.05). These data show the phenotypic changes in the cellular components of BALF during the course of natural MYY infection, and suggest a state of activation of BALF lymphocytes, and a pulmonary compartmentalisation of the cellular immune response during the course of the disease.

The stage of activation of BALF and PB lymphocytes in MW-infected and control sheep was investigated by using dual-colour flow cytometry and several parameters of lymphocyte activation. Upregulation of DR and DQ MHC Class II molecules was present in BALF of MWinfected animals, with no changes in cell size and complexity or increased expression of IL-2R, suggesting an impaired process of lymphocyte activation in BALF lymphocytes of these animals. There was no evidence of lymphocyte activation in PB.

To investigate if the impaired lymphocyte activation observed during the course of the natural disease was maintained under in vitro conditions, the response of BALF and PB lymphocytes to in vitro activation by exogenous mitogen was studied. BALF and PB lymphocytes from control and MW-infected animals were cultured for three days after Con A stimulation, and EL-2R surface expression was quantified by dual-colour flow cytometry. Cultured BALF T lymphocytes from MW-infected animals, after in vitro mitogen stimulation, expressed lower IL-2R than those of controls. These results suggest a dysfunction on cellmediated immunity during maedi.